Pembuatan Yoghurt Susu Sapi Segar dengan Penambahan Puree Ubi Jalar Ungu - Sari Mustika; Sedarnawati Yasni; Suliantari Suliantari (Jurnal Pendidikan Teknologi Kejuruan, 2019)
Making fresh cow's milk yogurt with the addition of purple sweet potato puree is diversification in making yogurt. The purpose of this study was to analyze the effect of adding purple sweet potato puree to pH, viscosity, total titrated acid and total dissolved solids in yogurt making. In this study the RAL experimental design (complete random design) was used to test pH, viscosity, total titrated acid and total dissolved solids with 3 treatments and 2 replications, then proceed with the Tukey real difference test if there were significant differences in each treatment. The treatment given is the addition of purple sweet potato puree as much as 4%, 6% and 8%. From the research results, a formula with 8% purple sweet potato puree was selected with the following characteristics: pH 4.14, total titrated acid 1.26%, viscosity 1154.5 cp, total dissolved solids 2.2o Brix, and total lactic acid bacteria 1.25x109 cfu / ml .